The Variants of Image-Bearing Word- Combinations in Old Armenian - KHACHATRIAN, LALIK (Bulletin of Yerevan University B: Philology, 2021)
The variants of image-bearing word-combinations in Old Armenian are characterized by specific models, which are divided into the following types: (lexical, սպիտակ որպէս զձիւն // սպիտակ իբրեւ զկաթն. white as snow. white as milk), grammatical (նման Աստուծոյ // որպէս զԱստուած. like the god // as a god), quantitative (քաղցր իբրև զմեղր // քաղցր քան զխորիսխ մեղու sweet as honey // sweet like a comb of honey). The ways of expressing the dominant components, the grammatical features of dependent members and the combinability of prepositions play an important role in the formation of these variants.